Uso de terapia floral para ansiedade em estudantes de medicina : um ensaio clínico randomizado - Oliveira, Allanna Stephany Cordeiro de (2024)
Anxiety is our body's natural response, and its behavior is relevant to psychosomatic disorders. Faced with this problem, treatment for anxiety disorders continues to come in different ways. A compromise approach includes one or more psychopharmacological interventions, such as anxiolytics and/or psychotherapy. There is a growing demand for alternative therapies due to side effects induced by drugs and chemical dependency, in addition to complementary psychotherapy, Brazil has gradually introduced complementary practices through the Unified Health System (SUS), which includes complementary practices of quality, safety and effectiveness, taking into account the approval of the practice by society. Floral therapy is an ideal complement to any treatment that seeks to balance the patient's emotions, that is, a treatment based on the principle that the mind produces illness. Therefore, the study aimed to analyze the effects of flower therapy on anxiety and quality of life of health students. In which, two research studies were developed, firstly a systematic review to understand the benefits of flower therapy in individuals with anxiety, selecting 7 randomized clinical trials that reported the use of flower therapy, with the average age of their sample between 22.1 -40.5 years, and with groups between 29-102 participants, the objectives had points in common that were to analyze anxiety or stress, however, the population was diverse: students, teachers, women in labor and individuals in general. In the studies, it was possible to observe that flower remedies reduced stress, helping to achieve psychological and physical well-being, promoting each participant's ability to look at themselves and find balance with their self, characteristics that helped with self-control and encouragement. , unraveling limiting beliefs, allowing them to identify differences in mental and physical exhaustion. The second research is a double-blind, placebo-controlled, 4-week randomized clinical trial. The research took place at the Federal University of Paraíba (UFPB), between October and December 2022. Students of both sexes, aged between 18 and 59, enrolled from the first to the fourth year of the Medicine course, were eligible and included. from UFPB. Data collection was carried out using pre- and post-test questionnaires, with scales that addressed the research themes. The information obtained through the instruments was processed in the statistical program SPSS® Statistics version 25.0, with a significance level of 5% for all variables. The research included 90 participants, the majority of whom were white females in the intervention group and brown/black in the placebo group. The results showed that flower therapy is effective in reducing anxiety, as well as increasing quality of life. in physical, psychological aspects, social relationships and the environment. Therefore, it is concluded that flower therapy can be beneficial for students who have anxiety, in order to help them improve their daily activities.